US-RUSSIAN RELATIONS: BALANCING INTERESTS AND FEARS - Nikolic, Danijela (Political Review, 2025)
The fluctuation of US-Russian relations points to the fact that the correlation between these two countries represents one of the most significant and complex aspects of global politics, and that it is intertwined with phases of cooperation and rivalry, which continuously influence the formation of the global order. With the bloc division of the world into “East” and “West”, it was precisely the relations between these two powers that determined events and shaped political circumstances on the world geopolitical scene. With each change of administration, the competitive relationship between Washington and Moscow has continued, accompanied by limited enthusiasm for cooperation, mainly in the domain of arms control and the fight against global threats. The aim of this paper is to analyze the initial phase of improving relations, fueled by the “reset” tendency, as well as the outbreak of a new wave of tensions in US-Russian relations, identify key events and policies that shaped relations between the United States and the Russian Federation at the beginning of the 21st century, as well as to identify the causes of the failure of the “reset”. The contrasting foreign policy discourses of Moscow and Washington, the rise of the BRICS, and the expansion of China have posed a significant challenge to the liberal order led by the US. Using content analysis and discourse analysis methods, the author will provide insight into the factors that have contributed to the deterioration of US-Russian relations, with a focus on the opposing tendencies of these two states in foreign and domestic policy.
Keywords: United States; Russian Federation; “reset”; geopolitics; BRICS; China